A opinião veiculada no discurso da revista Caros amigos: uma análise à luz da análise crítica do discurso e da linguística sistêmico-funcional - Daniele de Oliveira (2013)
This thesis investigates how opinion is constructed in the discourse in Caros Amigos magazine. The focus is on the social actors mainstream media, Caros Amigos magazine itself, and the magazine readers. We therefore elected Critical Discourse Analysis, from Faircloughs assumptions and with theoretical support in Systemic Functional Linguistics as proposed by Halliday. Among the linguistic resourcesproposed in this theoretical approach, as guideline to our research we have selected the discourse genre, the transitivity system, the representation of social actors, and thematic structure present in this discourse. Thus, we tried to fill the gap in discourse studiesconcerning the analysis of the alternative media discourse, which, in general, is overlooked in relation to the mainstream media. Our corpus consists of fifteen editorials from Caros Amigos magazine and three op-eds from the same magazine. What puts this corpus together is the theme centralizing typical in journalism, whether in the mainstream media or in the very Caros Amigos. Assuming language is a system of choices available in a given social environment so that the user is able to perform social functions, we consider relevant the systemic functional understanding of language we adopt with intents of investigating how an opinion is constructed in the discourse in the Caros Amigos magazine. Our analyzes chiefly demonstrate (i) the circumstantial aspect and the use of the present tense can be considered characteristicsof the magazine's editorial, (ii) the assessment in this editorials plays key role in building a point of view in this discourse (iii) the representation of experience (material processes), classifications and definitions (relational processes), as well as the inclusion of other voices (verbal processes) constitute the structural basis of the discourse in themagazine, (iv) social actors mainstream media, Caros Amigos magazine, and magazine readers are generally related to material processes, which means they have roles primarily active in this discourse, (v) the frequent categorization of the mainstream media reveals its homogenization, generally not referred to in a specificway, unlike Caros Amigos magazine which is usually named, and (vi) that the thematic structure of the discourse in the magazine reveals the importance of social actor mainstream media in this discourse. We can thus emphasize the complexity of constructing a point of view conveyed through the discourse in Caros Amigos magazine, its ideological nature, and the importance of the Social Actor mainstream media in this context.